2006
DOI: 10.1007/s11064-006-9192-x
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Rapid Export of the Monochlorobimane–Glutathione Conjugate in Cultured Rat Astrocytes

Abstract: Monochlorobimane (MCB) is often used to visualize glutathione (GSH) levels in cultured cells, since it is quickly converted to a fluorescent GSH conjugate (GS-MCB). To test for consequences of MCB application on the GSH metabolism of astrocytes, we have studied rat astrocyte-rich primary cultures as model system. MCB caused a concentration dependent rapid decrease in the cellular GSH content. Simultaneously, a transient accumulation of GS-MCB in the cells was observed with a maximal content 5 min after MCB app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
(64 reference statements)
2
24
0
Order By: Relevance
“…This staining method is known to cause a temporary increase in GSH . Although the GSH–monochlorobimane complex is cleared efficiently from healthy tissue, its efflux might be impaired in the metabolically challenged penumbra, because the efflux is dependent on ATP consumption . Taking this together with the choice of different ROIs in our study, we believe that this may be the best explanation for these seemingly contradictory findings.…”
Section: Discussionmentioning
confidence: 77%
“…This staining method is known to cause a temporary increase in GSH . Although the GSH–monochlorobimane complex is cleared efficiently from healthy tissue, its efflux might be impaired in the metabolically challenged penumbra, because the efflux is dependent on ATP consumption . Taking this together with the choice of different ROIs in our study, we believe that this may be the best explanation for these seemingly contradictory findings.…”
Section: Discussionmentioning
confidence: 77%
“…In addition to a direct Mrp1-mediated GSH export, a Mrp1-mediated export of the GSH-containing intermediates of the formaldehyde metabolism, S-hydroxymethyl-GSH and S-formyl GSH, could also contribute to the observed accelerated GSH export in formaldehyde-treated neurons, as GSH conjugates are known as good Mrp1 substrates (Cole and Deeley 2006;Waak and Dringen 2006). As a result of their known lability (Uotila 1981;Krieter et al 1985) both S-hydroxymethyl-GSH and S-formyl-GSH are likely to liberate GSH rapidly after export from the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both the inhibition of glycolysis and the decline in cellular GSH could contribute to the observed toxicity of IAA and IA after longer exposure to astrocytes. Since cultured astrocytes are able to survive depletion of their cellular GSH for several hours (Waak and Dringen, 2006), the cellular GSH deprivation appear not to be the primary cause of the delayed cell death observed after treatment with the thiol reagents. It is more likely that the depletion of cellular ATP that has been reported for cultured brain cells at least for the treatment with IA (Hernandez-Fonseca et al, 2008; Nodin et al, 2005; Ogata et al, 1995) is responsible for the observed cell death after exposure to IAA or IA.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured astrocytes contain GSH in a cytosolic concentration of 8 mM (Dringen and Hamprecht, 1998). These cells rely on a high GSH concentration for the rapid clearance of peroxides (Dringen et al, 2005; Liddell et al, 2006a,b) for the resistance against oxidative stress (Bi et al, 2008; Bishop et al, 2007; Gegg et al, 2003, 2005; Giordano et al, 2008) and for the GSH-dependent detoxification of xenobiotics (Kubatova et al, 2006; Sagara and Sugita, 2001; Waak and Dringen, 2006). …”
Section: Introductionmentioning
confidence: 99%